PENGARUH STATUS SOSIAL DAN LITERASI EKONOMI TERHADAP KEPUTUSAN KONSUMSI MAHASISWA PENDIDIKAN EKONOMI - Siti Hardianti; Achmadi Achmadi; Husni Syahrudin (Universitas Tanjungpura, 2019)
AbstractThis study aims to determine whether there is an influence of social status and economic literacy on consumption decisions of Economics Education students. This study uses a descriptive method with a quantitative approach. What will be used is Interrelationship Studies. The study population was Untan Economic Education students (regular) totaling 251 students, and the total sample in this study was 146 students. Data collection techniques that will be used in this study are indirect communication techniques, measurement techniques and documentary techniques. Data collection tools used in this study are measurement tests, questionnaires or questionnaires, visual documentation tools. The analysis of the results of the study was carried out using Multiple Linear Regression Analysis. There is a significant effect of social status on consumption decisions, economic literacy on consumption decisions, simultaneously having an influence on social status and economic literacy on consumption decisions. This means that the better social status and knowledge about the economy, the consumption decision will increase. If social status and economic literacy are low, the consumption decisions will also be low.Keywords: social status, economic literacy, student consumption decision